Antioxidant properties and inhibition of lipid formation in 3T3‐L1 adipocytes of in vitro digested mageu, a commercial sample. Issue 10 (14th September 2021) - Nathu, Haleema; Mbuyama, Kabuzi R.; Adarkwah‐Yiadom, Martin; Serem, June C.; Ibrahim, Mohammed Auwal; Duodu, Kwaku G.; Gaspar, Anabella R. M.; Bester, Megan J.
Abstract: Mageu is a fermented, non‐alcoholic maize‐derived product unique to southern Africa. The aim of this study was to identify the health benefits of a polyphenolic extract of commercially produced mageu related to the antioxidant properties and effects on lipid accumulation in differentiated 3T3‐L1 adipocytes. A pooled sample of mageu Number 1 brand (original non‐flavored) was subjected to in vitro gastroduodenal digestion (GDD). Reverse phase high‐performance liquid chromatography of unfractionated undigested (UD) and GDD mageu revealed that with digestion there was an increased extraction of 1.2, 1.83, 1.45, 4.86, and 3.17‐fold of caffeic acid, 3, 4‐dihydroxybenzoic acid, p ‐coumaric acid, 4 hydroxybenzoic acid and ferulic acid, respectively. An associated increase in the total phenolic acid content and antioxidant activity in the <3 kDa fraction was obtained. In contrast with digestion, inhibition of advanced glycation end products formation and low‐density lipoprotein oxidation was found in the <30 kDa fraction indicating the contribution of larger, possibly feruloylated polysaccharides, to activity. Cellular antioxidant activity in Caco‐2 cells was >90% for all UD fractions, but with GDD was reduced. All fractions had low scavenging of nitric oxide in the lipopolysaccharide/murine cell model. Exposure of 3T3‐L1 adipocytes to all the UD and GDD mageu fractions (at 1% and 10% concentrations) during differentiation resulted in at least a 35% reduction in lipid accumulation, which was not associated with a loss of cellular viability. In conclusion, mageu, UD, and subjected to GDD contains phenolic acids with beneficial bioactive properties that contribute to antioxidant activity and reduces lipid accumulation in adipocytes. Practical applications: Mageu is a non‐alcoholic fermented maize product which when digested has increased bioactivity. Its reported health benefits are due to its caloric content therefore the practical application of this research is to validate the scientific benefits of this food and encourage increased consumption of this functional food. This is especially important in the context of the South African population where this product is widely consumed as increasing obesity is associated with an increased risk of non‐communicable disease. Furthermore, as a non‐alcoholic drink, consumption can be promoted for all ages' groups and religions, and a commercialized manufacture processes can be optimized to increase phenolic acid release. Abstract : Mageu is a non‐alcoholic fermented maize product that contains phenolic acid content, has chemical and cellular antioxidant activity and reduces lipid accumulation in differentiating adipocytes. After simulated in vitro digestion, mageu has both increased extracted phenolic acid content, increased anti‐glycation activity, increased anti‐peroxidation activity and increased inhibition of lipid accumulation in differentiating adipocytes. Pre and post digestion, non‐significant anti‐inflammatory activity is observed.